Single-cell RNA sequencing and proteomics uncover SIRPα-CD47 immune checkpoint and glycolysis-driven immune evasion in cardiac myxoma - Zhu, Xinyuan; Gao, Qingle; Dai, Xintong; Sun, Baofa; Li, Yanping; Zhai, Hongyan; Shan, Changliang (Frontiers in Immunology, 2025)
Cardiac myxoma (CM), a rare primary cardiac tumor, poses significant life-threatening risks. Current CM research has remained largely limited to clinical case observations and pathological analyses, thus restricting its clinical therapeutic impact. Fundamental research should be urgently strengthened to better support future CM treatment strategies. In this work, single-cell sequencing is used to elucidated the intricate cellular composition of the CM microenvironments. The mechanisms of heart myxoma cell growth are investigated via proteomics and organoid models, while our western blot analysis reveals cardiac myxoma’s immune evasion strategies. This study successfully characterizes diverse cell types within the CM microenvironment. Notably, ap-CAF cells are found to effectively recruit immune cells via chemokine secretion, fostering immune microenvironment formation. The work’s pseudotime trajectory analysis also demonstrates that CM tumor cells derive from mesenchymal stem cells. Additionally, this work demonstrated that the glycolysis pathway is significantly activated and fuels CM cell growth. Tumor cells exploit the SIRPα-CD47 immune checkpoint to evade the immune system by inhibiting antigen-presenting cell phagocytosis. Tumor-associated macrophages (TAMs) concurrently assume M2 polarization and suppress autoimmune activity through IL-10. This research comprehensively examines CM’s microenvironmental cellular architecture, metabolic features, and immune escape mechanisms. These work’s findings not only deepen the current understanding of CM’s biological nature but also offer vital theoretical foundations for developing safer, more effective CM therapies.